Application of Genetics and Genomics in Poultry Science 2018
DOI: 10.5772/intechopen.78005
|View full text |Cite
|
Sign up to set email alerts
|

Avian Cardiovascular Disease Characteristics, Causes and Genomics

Abstract: Cardiovascular disease is common in avian species and increasing commercial economic losses and demand for healthcare in the household/smallholding veterinary sector has resulted in increased research into these disorders. This in turn has highlighted the importance of breeding, genetic testing and possibilities for future prognostic and diagnostic testing. Research into avian cardiovascular genetics has rapidly accelerated. Previously much work was undertaken in mammals with information extrapolated and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 91 publications
0
7
0
4
Order By: Relevance
“…Cardiovascular defects in birds have been investigated far less than in mammals, but have been described for numerous species (see Kubale et al, 2018). Ventricular septal defects have been described in a juvenile houbara bustard (Chlamydotis undulata macqueenii) (Bailey & Kinne, 2001) and for penguins as well as various species of caged birds (Laughlin et al, 2016).…”
Section: (A) Intracardiac Shuntsmentioning
confidence: 99%
“…Cardiovascular defects in birds have been investigated far less than in mammals, but have been described for numerous species (see Kubale et al, 2018). Ventricular septal defects have been described in a juvenile houbara bustard (Chlamydotis undulata macqueenii) (Bailey & Kinne, 2001) and for penguins as well as various species of caged birds (Laughlin et al, 2016).…”
Section: (A) Intracardiac Shuntsmentioning
confidence: 99%
“…Cardiovascular disease is common in avian species (Beaufrère et al, ). The increase in commercial economic losses and demand for healthcare in veterinary centres has resulted in increased research investigating these disorders (Kubale, Merry, Miller, Diaz, & Rutland, ). Alterations in nutritional status may result in cardiac structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of complete understanding of the nutritional requirements of captive parrots, malnutrition is a concern in this species (Heatley & Cornejo, ). Additionally, in commercial breeding, changes in the avian heart cause concern, and the impact of diet on the risk of heart failure in broiler chickens has been investigated to design nutritional plans to maximize growth while reducing the risk of cardiac failure (Kubale et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ekweozor et al (2002) noted that hens exposed to crude oil had diminished growth, egg production, egg quality, and hatchability. Kubale et al (2018) and Jiang et al (2019) reported incidences of cardiovascular diseases such as atherosclerosis, right ventricular failure, and developmental cardiotoxicity in poultry.…”
Section: Hydrocarbon Pollution and Physiological Responses Of Poultrymentioning
confidence: 99%